Selection of corn populations based on early biomass production under saline stress conditions - Félix-Lizárraga, Jesús Ulises; Ruiz-Torres, Norma Angélica; Rincón-Sánchez, Froylán; Sánchez-Ramírez, Francisco Javier; Borrego-Escalante, Fernando; Benavides Mendoza, Adalberto (Revista Mexicana de Ciencias Agrícolas, 2023)
Native corn populations have attributes that differentiate them because of their area of adaptation to adverse biotic and abiotic conditions that can be used in selection schemes. The objectives of the present research were to analyze dry matter production in early stages of development and selection of corn populations under conditions of salinity stress. One hundred eighteen corn populations of the Ratón race and two controls (hybrids) were evaluated in trials conducted in greenhouse in two contrasting environments in 2021 (with and without saline stress). Dry root weight, dry stem weight and chlorophyll content were determined. In the environments, statistical differences were found in dry stem weight (p≤ 0.01) and chlorophyll content (p≤ 0.05), while in DRW there was no difference. In the genotypes (populations and controls) statistical differences (p≤ 0.01) were found for the variables of dry weight, except in the chlorophyll content. There was no evidence of interaction of genotypes × environments in any of the variables studied. Saline stress conditions had an effect relative to non-stress conditions with a reduction of 25.9% in DRW and of 47.5% in dry stem weight. It is determined that there is genetic variation in the studied populations of the Ratón race for dry root weight and dry stem weight with an estimate of broad-sense heritability of 0.6 and 0.62, respectively, which allows selection of genotypes in the early stage of development. Of the 25 superior genotypes, 10 were identified in the favorable environment (control), six in the stress (salinity tolerant) environment and nine with an average behavior across environments.
Keywords: Zea mays L.; race Raton; salinity stress; genetic diversity